Rereading Huizinga : autumn of the middle ages, a century later - Arnade, Peter J.; Howell, Martha C.; Lem, Anton van der (Amsterdam University Press, 2019)
This edited volume is a reappraisal of the legacy and historiographical impact of Johan Huizinga's 1919 masterwork for the centenary of its publication in the field of medieval history, art history, and cultural studies.